Removal of sulfur from sulfur-bearing natural gas to produce clean jet fuel. (16th September 2016) - Al Sasi, Basil Omar; Demirbas, Ayhan
ABSTRACT: Despite the low percentage of trace level sulfur in natural gas (NG), its use as a jet fuel for reduction from the ultra level is very important. Clean and efficient NG as a fuel has major advantages and importance. If the sulfur content of natural gas will decrease in how much it is substantially upgraded. The main problems and difficulties encountered method of removing minor amounts of sulfur remaining in gases after conversion of the major portion of the sulfur content of the gas to elemental sulfur by the Claus or Stretford methods, or any method. Low-quality NG contains hydrogen sulfide, carbon dioxide, and nitrogen, but is not suitable for treatment using current conventional gas treating methods due to economic and environmental challenges. To remove sulfur from natural gas as the most common on the Claus process is applied. However, the Claus process itself is not sufficient for removal of sulfur in the ultra level. The tail gas from the Claus reaction is then passed through a catalytic hydrogenation reactor together with a supply of hydrogen to reduce the sulfur and sulfur compounds to hydrogen sulfide. As a results, hydrogen sulfide is completely removed from the NG streams by washing with alkanolamine solutions.